1995
DOI: 10.1073/pnas.92.13.5845
|View full text |Cite
|
Sign up to set email alerts
|

Minimal epitopes expressed in a recombinant polyepitope protein are processed and presented to CD8+ cytotoxic T cells: implications for vaccine design.

Abstract: The epitopes recognized by CD8+ cytotoxic T lymphocytes (CTL) are generated from cytosolic proteins by proteolytic processing. CD8+ a3 cytotoxic T lymphocytes (CTL) recognize short peptides (epitopes) associated with specific alleles of the class I major histocompatibility complex (1). The peptide epitopes are mainly generated from cytosolic proteins by proteolysis, a process believed to involve the multicatalytic proteosome complex (2-8). The influence of sequences flanking CTL epitopes on the proteolytic pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
64
0
1

Year Published

1995
1995
2011
2011

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 130 publications
(67 citation statements)
references
References 34 publications
(29 reference statements)
2
64
0
1
Order By: Relevance
“…It can be argued that MCA-peptides are artificial substrates and therefore have no bearing on the intracellular production of peptides for immune presentation. The same arguments can be used to evaluate other studies where longer, non-fluorogenic peptides have been employed [32][33][34]. The nature of endogenous precursors to presented peptides remains unclear (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…It can be argued that MCA-peptides are artificial substrates and therefore have no bearing on the intracellular production of peptides for immune presentation. The same arguments can be used to evaluate other studies where longer, non-fluorogenic peptides have been employed [32][33][34]. The nature of endogenous precursors to presented peptides remains unclear (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…The problem of EBV reactivation in pediatric bone marrow transplant patients can be controlled by transferring a mixture of in vitro-expanded virus-specific CD4 ϩ and CD8 ϩ T cell lines (14), but this expensive and technically demanding procedure will always be of limited application. Efforts are also being made to develop a peptide-based vaccine for EBV, the idea being that a primed CD8 ϩ T cell response will help to limit the initial phase of the infectious process and allow the rapid emergence of immune CD4 ϩ T cells and antibody (15,16). Even if such a vaccine does not provide sterilizing immunity, it might serve to boost CD8 ϩ T cell memory before transplant (5,15,16) and to prevent the debilitating infectious mononucleosis (IM) syndrome (17,18) seen characteristically when EBV is first encountered during adolescence.…”
mentioning
confidence: 99%
“…Efforts are also being made to develop a peptide-based vaccine for EBV, the idea being that a primed CD8 ϩ T cell response will help to limit the initial phase of the infectious process and allow the rapid emergence of immune CD4 ϩ T cells and antibody (15,16). Even if such a vaccine does not provide sterilizing immunity, it might serve to boost CD8 ϩ T cell memory before transplant (5,15,16) and to prevent the debilitating infectious mononucleosis (IM) syndrome (17,18) seen characteristically when EBV is first encountered during adolescence. This immunization strategy is tested here with the ␥HV-68 model (19,20).…”
mentioning
confidence: 99%
“…In various systems, either replicative such as vaccinia or non-replicative such as VLPs produced in yeast (Ty VLPs) (Gilbert et al, 1997) or bacterial toxins reaching the cytosol of APCs (Fayolle et al, 2001), the use of polyepitope chains containing multiple CD8 + T-cell epitopes has been reported for vaccine design (Thomson et al, 1995;Woodberry et al, 1999). In these studies, no influence of the flanking sequences was observed, since the epitopes were linked together and all seemed to be correctly processed.…”
Section: Discussionmentioning
confidence: 99%
“…Although it was initially established that some flanking sequences could prevent the proteolytic generation of the epitope (Del Val et al, 1991), it is not clear whether the presence of natural flanking sequences is necessary for the correct cleavage of the epitope. In fact, several studies have demonstrated the efficient presentation of CTL epitopes regardless of their context (Gilbert et al, 1997;Thomson et al, 1995).…”
Section: Introductionmentioning
confidence: 99%